Development of a thermoeconomic methodology for the optimization of biodiesel production - Part I: Biodiesel plant and thermoeconomic functional diagram - Coronado, Christian Rodriguez; Tuna, Celso Eduardo [UNESP]; Zanzi, Rolando; Vane, Lucas F. [UNESP]; Silveira, José Luz [UNESP] (My University, 2013)
This work developed a methodology that uses the thermoeconomic functional diagram applied for allocating the cost of products produced by a biodiesel plant. The first part of this work discusses some definitions of exergy and thermoeconomy, with a detailed description of the biodiesel plant studied, identification of the system functions through Physical Diagram, calculation of the irreversibilities of the plant, construction of the Thermoeconomic Functional Diagram and determination of the expressions for the plant's exergetic functions. In order to calculate the exergetic increments and the physical exergy of certain flows in each step, the Chemical Engineering Simulation Software HYSYS 3.2 was used. The equipments that have the highest irreversibilities in the plant were identified after the exergy calculation. It was also found that the lowest irreversibility in the system refers to the process with a molar ratio of 6:1 and a reaction temperature of 60 °C in the transesterification process. In the second part of this work (Part II), it was calculated the thermoeconomic cost of producing biodiesel and related products, including the costs of carbon credits for the CO2 that is not released into the atmosphere, when a percentage of biodiesel is added to the petroleum diesel used by Brazil's internal diesel fleet (case study). © 2013 Elsevier Ltd. All rights reserved.
Keywords: Biodiesel; Diagram; Exergy; Glycerin; Irreversibility; Biodiesel production; Engineering simulation; Functional diagrams; Reaction temperature; Related products; Transesterification process; Carbon dioxide; Computer software; Costs; Glycerol